PENGARUH PROFITABILITAS, LIKUDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN MELALUI MODERASI INTELLECTUAL CAPITAL - Ardra Radhyan Hafidh; Hero Priono (Jurnal Proaksi, 2022)
Company performance can be seen from the company value which is a benchmark for managers and investors in perceiving the state of the company. The purpose of this study is to empirically examine the effect of profitability, liquidity and leverage on company value with intellectual capital as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is classified as quantitative research. The type of data used is secondary data in the form of annual financial reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period downloaded from the official website of the Indonesia Stock Exchange. The technique used for sampling is purposive sampling method and the method used for hypothesis testing is inferential statistics. The findings of this study indicate that the Profitability variable on Company Value has a positive and significant effect, the Liquidity variable has a negative and insignificant effect on Company Value and the Leverage variable has a negative and significant effect on Company Value. Then the moderating variable Intellectual Capital proved unable to moderate the relationship between Profitability and Liquidity, while the moderating variable Intellectual Capital was proven to be able to moderate the relationship between Leverage and Company Value. Keywords: Profitability, Liquidity, Leverage, Intellectual Capital